Isolation and characterization of human CXCR4-positive pancreatic cells - Koblas, T; Zacharovová, K; Berková, Z; Mindlová, M; Girman, P; Dovolilová, E; Karasová, L; Saudek, F (Folia biologica, 2007)
The existence of an adult PSC that may be used in the treatment of diabetes is still a matter of scientific debate as conclusive evidence of such a stem cell in the adult pancreas has not yet been presented. The main reason why putative PSC has not yet been identified is the lack of specific markers that may be used to isolate and purify them. In order to increase the list of potential PSC markers we have focused on the human pancreatic cells that express cell surface receptor CXCR4, a marker of stem cells derived from different adult tissues. Here we report that CXCR4-positive pancreatic cells express markers of pancreatic endocrine progenitors (neurogenin-3, nestin) and markers of pluripotent stem cells (Oct-4, Nanog, ABCG2, CD133, CD117). Upon in vitro differentiation, these cells form ILCC and produce key islet hormones including insulin. Based on our results, we assume that CXCR4 marks pancreatic endocrine progenitors and in combination with other cell surface markers may be used in the attempt to identify and isolate PSC.
Keywords: dospělí; C-Peptide; glukagon; Nestin; Adult; nestin; Receptors, CXCR4; buněčná diferenciace; lidé; fluorescenční protilátková technika; Fluorescent Antibody Technique; receptory CXCR4; pankreas; messenger RNA; Insulin; Intermediate Filament Proteins; kultivované buňky; proteiny nervové tkáně; Glucagon; RNA, Messenger; separace buněk; regulace genové exprese; Cells, Cultured; Nerve Tissue Proteins; Leukemia Inhibitory Factor Receptor alpha Subunit; Aged; Cell Separation; receptor leukemického inhibičního faktoru - alfa-podjednotka; lidé středního věku; Cell Differentiation; senioři; Gene Expression Regulation; Pancreas; C-peptid; inzulin; proteiny intermediálních filament; Middle Aged; Humans